1999
DOI: 10.1523/jneurosci.19-20-09016.1999
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Population Representation of Retinal Location: Neuronal Interaction Dynamics in Cat Primary Visual Cortex

Abstract: Neuronal interactions are an intricate part of cortical information processing generating internal representations of the environment beyond simple one-to-one mappings of the input parameter space. Here we examined functional ranges of interaction processes within ensembles of neurons in cat primary visual cortex. Seven "elementary" stimuli consisting of small squares of light were presented at contiguous horizontal positions. The population representation of these stimuli was compared to the representation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 56 publications
8
92
1
Order By: Relevance
“…We additionally found that response profiles for darkening and brightening were equal in size ( ϭ 1.99 Ϯ 0.1 mm SEM, values along major axis of the Gaussian fits) except for the square brightening on a dark background ( ϭ 1.70 Ϯ 0.09 mm SEM, p ϭ 0.018, two-sided Wilcoxon signed-rank test). This indicates that a smaller pool of neurons is recruited in the latter condition, potentially leading to less effective gain control (Sit et al, 2009) or reduced lateral suppression (Ferster, 1986;Nelson, 1991;Jancke et al, 1999), which in turn may contribute to the generation of larger receptive fields for lights on dark background than observed for opposite contrasts and brighter backgrounds (Kremkow et al, 2014). Altogether, we show that for an identical amount of change in stimulus luminance, population activity in response to stimulus darkening dominated responses to brightening during response rise times followed by earlier decay (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We additionally found that response profiles for darkening and brightening were equal in size ( ϭ 1.99 Ϯ 0.1 mm SEM, values along major axis of the Gaussian fits) except for the square brightening on a dark background ( ϭ 1.70 Ϯ 0.09 mm SEM, p ϭ 0.018, two-sided Wilcoxon signed-rank test). This indicates that a smaller pool of neurons is recruited in the latter condition, potentially leading to less effective gain control (Sit et al, 2009) or reduced lateral suppression (Ferster, 1986;Nelson, 1991;Jancke et al, 1999), which in turn may contribute to the generation of larger receptive fields for lights on dark background than observed for opposite contrasts and brighter backgrounds (Kremkow et al, 2014). Altogether, we show that for an identical amount of change in stimulus luminance, population activity in response to stimulus darkening dominated responses to brightening during response rise times followed by earlier decay (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such a spatially organized interaction scheme has been originally proposed to explain localized activation patterns in small pieces of neuronal tissue [58,2]. It has later been applied to model various functionalities in the perceptual and the motor domain (e.g., [41,10,61,37,39]). For the present modeling work, we adopt for each network layer a center-surround organization of recurrent interactions as a well studied mechanism underlying persistent activity patterns.…”
Section: Model Detailsmentioning
confidence: 99%
“…Although previous studies have provided important insights into the temporal and spatial dynamics of cortical interactions (Simons, 1985;Armstrong-James and George, 1988;Simons and Carvell, 1989;Brumberg et al, 1996;Ghazanfar and Nicolelis, 1997;Jancke et al, 1999), interpretations of these findings are limited because integration ascribed to the cortex may in part be attributable to subcortical processes. Whatever the nature of subcortical processes on ascending whisker information, cortical interactions may be addressed by exploiting the role the corpus callosum plays in integrating sensory information that is lateralized subcortically.…”
Section: Bilateral Interactions In Simentioning
confidence: 99%